Anthracite-based hard carbon negative electrode sodium storage material as well as preparation method and application thereof

The preparation of anthracite-based hard carbon negative sodium storage material by combining alkali activation method and chemical oxidation method is solved, and the problems of low sodium storage capacity of carbon materials and low first-time Coulomb efficiency in the prior art are solved, and efficient sodium ion battery performance is achieved.

CN119430126APending Publication Date: 2025-02-14CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410291632.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The carbon material obtained by direct pyrolysis of existing anthracite has a low sodium storage capacity in sodium ion batteries, and the first time the Coulomb efficiency is low, which affects the battery performance.

Method used

Anthracite-based hard carbon negative sodium storage material was prepared by combining alkali activation method and chemical oxidation method. The specific steps include: using anthracite as the substrate, preparing porous carbon intermediates through alkali activation method, followed by oxidation modification, and finally obtaining hard carbon materials through high-temperature carbonization.

Benefits of technology

The first coulomb efficiency and sodium storage capacity of hard carbon materials have been significantly improved, the first charging capacity reaches 325.2mAh g-1, the first coulomb efficiency reaches 92.2%, and the capacity retention rate after 150 cycles is 96.1%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430126A_ABST
    Figure CN119430126A_ABST
Patent Text Reader

Abstract

The invention discloses an anthracite-based hard carbon negative electrode sodium storage material as well as a preparation method and application thereof. The invention relates to the technical field of electrode materials. The preparation method comprises the following steps: S1, taking anthracite as a base material, and preparing a porous carbon intermediate by adopting an alkali activation method; s2, carrying out oxidation modification on the porous carbon intermediate; and S3, performing high-temperature carbonization on the oxidized and modified porous carbon intermediate to obtain the anthracite-based hard carbon negative electrode sodium storage material. The anthracite-based hard carbon negative electrode sodium storage material with high initial coulombic efficiency and high specific capacity is prepared by combining an alkali activation method and a chemical oxidation method, and the commercial hard carbon requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to an anthracite-based hard carbon negative electrode sodium storage material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have the advantages of good low temperature resistance, high safety, and low cost. They have broad application prospects in the fields of power batteries and large-scale energy storage, and form a complementary development with lithium-ion batteries. At present, the production capacity of sodium storage negative electrode materials in China is relatively limited, which is a key factor restricting the large-scale commercial application of sodium-ion batteries. Sodium storage negative electrode materials usually include carbon materials, titanium-based compounds, metal oxide / sulfide organic compounds, alloy materials, etc. Among them, hard carbon materials have become the most promising sodium-ion battery negative electrode materials due to their low cost, wide sources, and easy synthesis and preparation. The precursors for preparing hard carbon materials mainly include polymers, biomass, asphalt and anthracite. Among them, the cost and process difficulty of polymer hard carbon are relatively high, and the process difficulty of biomass hard carbon is small, but the carbon yield is low and the batch stability is poor. Compared with other precursors, anthracite has the advantages of high carbon content, low ash content, and low cost. However, the carbon material obtained by direct pyrolysis of anthracite has a low sodium storage capacity and a low first coulomb efficiency, which seriously affects the performance of the battery. In the initial cycle of a sodium-ion full battery, hard carbon with low first coulombic efficiency will consume a large amount of sodium provided by the positive electrode. In order to match the sodium consumption, the weight of the positive electrode needs to be increased, but this will seriously restrict the energy density of the battery. Therefore, the development of a preparation method for coal-based hard carbon sodium storage materials with high first coulombic efficiency and high sodium storage capacity is crucial for the large-scale application of sodium-ion batteries. Summary of the invention

[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to propose an anthracite-based hard carbon negative electrode sodium storage material with high first coulombic efficiency and high specific capacity, as well as a preparation method and application thereof.

[0004] A method for preparing an anthracite-based hard carbon negative electrode sodium storage material of the present invention comprises the following steps:

[0005] S1. Using anthracite as a substrate, a porous carbon intermediate was prepared by an alkali activation method;

[0006] S2, oxidatively modifying the porous carbon intermediate;

[0007] S3. Carbonize the oxidatively modified porous carbon intermediate at high temperature to obtain an anthracite-based hard carbon negative electrode sodium storage material.

[0008] Furthermore, the specific operation of step S1 is: fully mixing the anthracite with the strong alkali, then transferring the powder to air or nitrogen for pre-pyrolysis, and the pre-pyrolysis product is ground and then acid-washed, washed with water, filtered, and dried to obtain a porous carbon intermediate after activation.

[0009] Furthermore, the strong base includes one or more of sodium hydroxide and potassium hydroxide.

[0010] Furthermore, the pre-pyrolysis temperature is 200-800°C; and\or: the pre-pyrolysis temperature is 400°C.

[0011] Furthermore, the pickling is performed by stirring and immersing in hydrochloric acid or sulfuric acid with a concentration of 1 to 6 mol / L.

[0012] Furthermore, the specific operation of step S2 is: using an oxidant to perform oxidation, introducing a large number of oxygen-containing functional groups, and obtaining an oxidatively modified porous carbon intermediate.

[0013] Furthermore, the oxidant is one or more of potassium permanganate and concentrated nitric acid.

[0014] Furthermore, the temperature of the high temperature carbonization in step S3 is 1000-2000°C; and\or: the temperature of the high temperature carbonization is 1400°C.

[0015] An anthracite-based hard carbon negative electrode sodium storage material prepared by the above-mentioned preparation method.

[0016] An application of the anthracite-based hard carbon negative electrode sodium storage material as described above is used as a negative electrode material for a sodium ion battery.

[0017] The present invention utilizes a structural modification method to regulate the oxygen-containing functional groups in the hard carbon precursor, and then the surface oxygen-containing functional groups are decomposed, removed or transformed during the carbonization process to form defects or closed micropores; these closed-pore structures can significantly improve the sodium storage capacity of the low-potential platform, reduce irreversible losses in the first cycle, and thus improve the first coulombic efficiency.

[0018] The present invention adopts a combination of alkali activation method and chemical oxidation method to prepare anthracite-based hard carbon. The alkali activation method can effectively remove the ash of coal and activate the porous carbon intermediate at the same time. The large specific surface area has a significant promoting effect on the next step of chemical oxidation method; the chemical oxidation method can improve the first coulomb efficiency and specific capacity of coal-based hard carbon. For example, the nitric acid oxidation method, the principle is that concentrated nitric acid introduces rich oxygen-containing functional groups, such as carbonyl, carboxyl, etc. The oxygen-containing functional groups will decompose, remove and transform during the high-temperature carbonization process, leaving a large number of defects or micropores. When the temperature is further increased, the rearrangement of carbon atoms and the curling of graphite microcrystals will cause the open micropores to evolve into closed micropores. The closed-pore structure plays an important role in the first coulomb efficiency and sodium storage capacity of hard carbon materials, so the electrochemical performance can be significantly improved by chemical oxidation.

[0019] The anthracite-based hard carbon negative electrode sodium storage material prepared by the present invention has a rich closed microporous structure and thus has excellent electrochemical performance. Its first charge capacity can reach 325.2 mAh g -1 The first coulombic efficiency can reach 92.2%, the cycle performance is good, and the capacity retention rate is 96.1% after 150 cycles.

[0020] The chemical oxidation method provided by the present invention can effectively regulate the oxygen-containing functional groups of coal-based carbon. During the high-temperature calcination process, the surface oxygen-containing functional groups are decomposed, removed or converted during the carbonization process to form defects or closed micropores. The oxygen-containing functional groups have a specific effect on the formation of closed micropores of hard carbon. These closed-pore structures can significantly improve the sodium storage capacity of the low-potential platform and reduce the irreversible loss in the first cycle, thereby improving the first coulombic efficiency.

[0021] The present invention combines an alkali activation method and a chemical oxidation method to prepare an anthracite-based hard carbon negative electrode sodium storage material with high first coulombic efficiency and high specific capacity, meeting the requirements of commercial hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure is a schematic flow chart of the preparation method of the anthracite-based hard carbon negative electrode sodium storage material of the present invention;

[0023] Figure 2 The XPS spectra of the porous carbon intermediate before and after oxidation in Example 1;

[0024] Figure 3 XRD pattern of anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1;

[0025] Figure 4 The first cycle charge and discharge curve of the anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1;

[0026] Figure 5 This is the cycle performance diagram of the anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1. DETAILED DESCRIPTION

[0027] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0028] Example 1

[0029] Figure 1 Schematic diagram of the process for preparing the anthracite-based hard carbon negative electrode sodium storage material of the present invention, as shown in Figure 1 As shown, the preparation method of the anthracite-based hard carbon negative electrode sodium storage material of the present invention is as follows:

[0030] Step 1: Grind 1.5 g of anthracite and 3.0 g of potassium hydroxide in an agate mortar, then transfer the powder to a muffle furnace for pre-pyrolysis at a temperature of 400 ° C and a heating rate of 5 ° C / min. Use an agate mortar to fully grind the pre-pyrolysis product into powder, soak it in 200 mL of 3 mol / L hydrochloric acid for pickling for 2h, then use a large amount of deionized water to wash until the pH is neutral, and finally filter and dry to obtain the activated porous carbon intermediate.

[0031] Step 2: The porous carbon intermediate obtained in the first step is oxidized using 100 mL of 14 mol / L concentrated nitric acid, and after being placed in a water bath at 60° C. for 3 h, it is washed with deionized water, filtered, and dried to obtain a chemically oxidized modified porous carbon intermediate.

[0032] Step 3: Transfer the porous carbon intermediate obtained in the second step to a high-temperature tube furnace and calcine it at 1400°C at a heating rate of 2°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0033] Figure 2 is the XPS spectrum of the porous carbon intermediate before and after oxidation in Example 1; Figure 2 It can be seen that the carboxyl and carbonyl contents of the porous carbon intermediates increased significantly after oxidation with concentrated nitric acid, indicating that the chemical oxidation method effectively introduced oxygen-containing functional groups.

[0034] Figure 3 XRD pattern of anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1; Figure 3 It can be seen that anthracite-based hard carbon has the bulging peak characteristics of amorphous carbon. The carbon layer interplanar spacing calculated by the Bragg formula (2dSinθ=nλ) is 0.38nm, which is within the interlayer spacing range suitable for sodium ion transmission and deintercalation (0.36-0.40nm).

[0035] Example 2

[0036] The difference between the embodiment and Example 1 is that the concentration of nitric acid in step 2 is 6 mol / L. The other steps are consistent with Example 1.

[0037] Example 3

[0038] The difference between the embodiment and Example 1 is that the concentration of nitric acid in step 2 is 10 mol / L. The other steps are consistent with Example 1.

[0039] Example 4

[0040] The implementation method is different from Example 1 in that the pre-pyrolysis temperature in step 1 is 300° C. The other steps are consistent with Example 1.

[0041] Example 5

[0042] The implementation method is different from Example 1 in that the pre-pyrolysis temperature in step 1 is 500° C. The other steps are consistent with Example 1.

[0043] Example 6

[0044] The difference between the embodiment and Example 1 is that the high temperature calcination temperature in step 2 is 1200° C. The other steps are consistent with Example 1.

[0045] Example 7

[0046] The difference between the embodiment and Example 1 is that the high temperature calcination temperature in step 2 is 1600° C. The other steps are consistent with Example 1.

[0047] Example 8

[0048] The difference between the implementation mode and Example 1 is that the oxidation method in step 2 is potassium permanganate oxidation, that is, the porous carbon intermediate obtained in step 1 is added to a 3 mol / L KMnO4 solution for oxidation for 3 hours. The other steps are consistent with Example 1.

[0049] Comparative Example 1

[0050] Different from Example 1, Comparative Example 1 does not use a chemical oxidation process for regulating the oxygen-containing functional groups in the porous carbon. The implementation steps are as follows:

[0051] Step 1: Grind 1.5 g of anthracite and 3.0 g of potassium hydroxide in an agate mortar, transfer the powder to a muffle furnace, and pre-pyrolyze in an air atmosphere at a temperature of 400 ° C and a heating rate of 5 ° C / min. Use an agate mortar to fully grind the pre-pyrolysis product into powder, soak it in 200 mL of 3 mol / L hydrochloric acid for pickling for 2h, and then use a large amount of deionized water to wash it until the pH is neutral. Finally, filter and dry it to obtain the activated porous carbon intermediate.

[0052] Step 2: Transfer the porous carbon intermediate obtained in the second step to a high-temperature tube furnace and calcine it at 1400°C at a heating rate of 2°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0053] Comparative Example 2

[0054] The difference between the implementation mode and comparative example 1 is that the coal-alkali ratio in step 1 is 1:0, while that in comparative example 1 is 1:2, that is, the anthracite is directly carbonized without alkali activation.

[0055] Comparative Example 3

[0056] The difference between the embodiment and comparative example 1 is that the coal-to-alkali ratio in step 1 is 1:1, while that in comparative example 1 is 1:2, and the addition amount is 1.5 g of anthracite and 1.5 g of potassium hydroxide. The other steps are the same as those in comparative example 1.

[0057] Comparative Example 4

[0058] The implementation method is different from Example 1 in that the oxidation method in step 2 is air oxidation, that is, the porous carbon intermediate obtained in step 1 is oxidized at 400° C. in air atmosphere for 2 h with a heating rate of 5° C. / min. The other steps are consistent with Example 1.

[0059] Comparative Example 5

[0060] The implementation method is different from Example 1 in that the oxidation method in step 2 is hydrogen peroxide oxidation, that is, the porous carbon intermediate obtained in step 1 is added to a 30% H2O2 solution and oxidized for 6 hours under 80°C water bath conditions. The other steps are consistent with Example 1.

[0061] Electrochemical performance test

[0062] The electrochemical performance of anthracite-based hard carbon negative electrode sodium storage material was tested by assembling button half-cells.

[0063] Electrode slurry was prepared using aqueous binder sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). Materials with a mass ratio of ion battery hard carbon negative electrode material: conductive carbon black: CMC: SBR = 91:2:2:5 were weighed, and an appropriate amount of ultrapure water was added and mixed thoroughly before being evenly coated on copper foil. After drying at 60°C in a forced air drying oven for 2 hours, the mixture was transferred to a vacuum oven at 80°C and dried for 10 hours. After that, circular electrode sheets with a diameter of 10 mm were cut to assemble button cells, in which sodium foil was used as the counter electrode, the diaphragm was glass fiber Whatman GF / D, and the electrolyte was 1M NaPF6in DIGLYME = 100 Vol%. The oxygen and moisture contents in the glove box were both less than 0.1 ppm, and the test current was 0.3C (defined as 300 mAg -1 =1C), the test voltage range is 0.001~3V, and the charge and discharge cycle test is carried out. Table 1 is the charge and discharge cycle test results of the embodiment and the comparative example.

[0064] Figure 4 The first cycle charge and discharge curve of the anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1 is as follows: Figure 4 As shown, the first charge capacity is 325.2 mAh g -1 , the first Coulombic efficiency is 92.2%.

[0065] Figure 5 This is a cycle performance diagram of the anthracite-based hard carbon negative electrode sodium storage material prepared in Example 1, as shown in Figure 5 As shown, the first coulombic efficiency is high and the cycle performance is excellent, with a capacity retention rate of 96.1% after 150 cycles.

[0066] Table 1 Charge and discharge cycle test results of the embodiments and comparative examples

[0067]

[0068] The following conclusions can be drawn from the results in the above table.

[0069] (1) From Examples 1, 2, and 3, it can be seen that as the concentration of nitric acid increases, the first effect gradually increases, which is related to the number of oxygen-containing functional groups introduced. The higher the concentration of nitric acid, the more oxygen-containing functional groups are introduced, which is conducive to the evolution and formation of a closed-cell structure.

[0070] (2) From Examples 1, 4, and 5, it can be seen that the pre-pyrolysis temperature also affects the performance, because the pre-pyrolysis temperature mainly affects the degree of alkali activation. At 300°C, the activation is not sufficient, the intermediate pore structure is not rich, and the subsequent closed pore formation is less, so the initial efficiency is low. At 500°C, the activation is sufficient, but the micropores formed in the intermediate may be too small, and the closed pores formed later are smaller.

[0071] (3) From Examples 1, 6, and 7, it can be seen that a suitable high-temperature calcination temperature needs to be selected. When the temperature is low, the closed pore size is small, which is not conducive to sodium storage. When the temperature is too high, the degree of graphitization of the hard carbon increases and the spacing between carbon layers decreases, which is not conducive to the transmission of sodium ions between layers, so the performance is significantly reduced.

[0072] (4) The product prepared in Comparative Example 1 has better performance than that in Examples 6 and 7 because the high temperature calcination temperature in Comparative Example 1 is more appropriate.

[0073] (5) From Comparative Examples 1, 2, and 3, it can be seen that the larger the coal-alkali ratio, the more fully activated, the richer the pore structure of the intermediate, and thus the better the performance. When the coal-alkali ratio is 1:2, the ash in the anthracite can be fully removed, improving the first efficiency and cycle performance of the hard carbon.

[0074] (6) From Examples 1 and 8, and Comparative Examples 4 and 5, it can be seen that not all oxidants can improve the electrochemical performance of anthracite-based hard carbon, and may even reduce it. This may be related to the position of the introduced oxygen-containing functional groups. For example, air oxidation and hydrogen peroxide oxidation may be non-destructive oxidations, and the position where the oxygen-containing functional groups are generated may exist at the edge of the carbon layer, which has no effect on the formation of closed pores; while nitric acid and potassium permanganate oxidant solutions may be destructive oxidations, and the position where the oxygen-containing functional groups are generated may exist on the basal surface of the carbon layer, which has a significant effect on the formation of closed pores. Therefore, it is necessary to select a suitable chemical oxidation technology.

[0075] For matters not mentioned above, the prior art applies.

[0076] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing anthracite-based hard carbon negative electrode sodium storage material, characterized in that: The steps include: S1. Using anthracite as a substrate, a porous carbon intermediate was prepared by an alkali activation method; S2, oxidatively modifying the porous carbon intermediate; S3. Carbonize the oxidatively modified porous carbon intermediate at high temperature to obtain an anthracite-based hard carbon negative electrode sodium storage material.

2. The method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to claim 1, characterized in that: The specific operation of step S1 is: thoroughly grind the anthracite and the strong alkali, then transfer the powder to air or nitrogen for pre-pyrolysis, grind the pre-pyrolysis product, pickle it, wash it with water, filter it, dry it, and then activate it to obtain a porous carbon intermediate.

3. The method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to claim 2, characterized in that: The strong base includes one or more of sodium hydroxide and potassium hydroxide.

4. The method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to claim 2, characterized in that: The pre-pyrolysis temperature is 200-800°C; and\or: the pre-pyrolysis temperature is 400°C.

5. The method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to claim 2, characterized in that: The pickling is carried out by stirring and immersing in hydrochloric acid or sulfuric acid with a concentration of 1 to 6 mol / L.

6. A method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to any one of claims 1 to 5, characterized in that: The specific operation of step S2 is: using an oxidant to perform oxidation, introducing a large number of oxygen-containing functional groups, and obtaining an oxidatively modified porous carbon intermediate.

7. The method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to claim 6, characterized in that: The oxidant is one or more of potassium permanganate and concentrated nitric acid.

8. A method for preparing an anthracite-based hard carbon negative electrode sodium storage material according to any one of claims 1 to 5, characterized in that: The temperature of the high temperature carbonization in step S3 is 1000-2000°C; and\or: the temperature of the high temperature carbonization is 1400°C.

9. An anthracite-based hard carbon negative electrode sodium storage material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the anthracite-based hard carbon negative electrode sodium storage material as claimed in claim 9, characterized in that: Used as negative electrode material for sodium-ion batteries.

Citation Information

Cited By

  • Lignite-based hard carbon negative electrode material, preparation method and application thereof

    CN120328524A